Comparative biomechanical analysis of monocortical and bicortical polyaxial screw rod fixation in canine lumbar vertebral stabilization - Julien Guevar; Benjamin Voumard; Robert Bergman; Christina Precht; Franck Forterre (Frontiers in Veterinary Science)
ObjectiveThis study aims to evaluate the biomechanical properties of polyaxial screws-rod fixation (PSR) in stabilizing a single vertebral motion unit (VMU) fracture model and to compare the effectiveness of different stabilization techniques such as monocortical and bicortical.MethodsA total of 12 thoracolumbar vertebral column specimens were harvested from canine cadavers. These specimens were divided into two groups based on the stabilization technique applied: a monocortical group and a bicortical group. Each group underwent biomechanical testing to assess flexion/extension and lateral bending motions. The range of motion (ROM), neutral zone (NZ), and stiffness were measured for each lumbar VMU in three conditions: intact, fractured with unilateral stabilization, and fractured with bilateral stabilization.ResultsIn the 3-column fracture model, PSR was unable to restore the ROM of an intact spine in flexion/extension. In lateral bending, only bilateral PSR successfully approached the ROM of the intact spine. Notably, PSR failures were observed in four specimens when applied as monocortical and unilateral stabilization.ConclusionThe findings indicate that even bilateral PSR does not fully restore the intact spine's ROM in canine fracture models, highlighting the need for further research to optimize stabilization techniques. The current study demonstrates that a single 3-column lumbar fracture model VMU cannot be adequately stabilized using PSR in a canine model, suggesting potential limitations in both monocortical and bicortical approaches.